From Traditional Teaching to Flipped Classroom Model: Exploring Acehnese EFL Students’ Perception - Juliana Juliana; Lathifatuddini Rusdi; Che Azunie Che Abdullah; Muhammad Nasir (Institut Agama Islam Negeri Lhokseumawe, 2025)
With the rapid advancement of educational technology, students increasingly adapt their learning styles to digital platforms; however, integrating technology effectively into English as a Foreign Language (EFL) instruction remains a pedagogical challenge. Although the flipped classroom model has been widely explored in global contexts, limited evidence exists on how EFL students in Indonesia—particularly in Aceh—perceive and respond to this approach. Contextual factors such as internet access, lecturer readiness, and students’ digital habits may influence its effectiveness, yet remain underexplored. This study employed a qualitative design to examine university students’ perceptions of the flipped classroom model in EFL learning. Data were collected from 85 students in the third to fifth semesters across three universities in Aceh, all of whom had prior experience with the flipped classroom. The findings revealed that 68% of students perceived the model as more engaging and 67% recommended it to peers, and students’ perceptions were generally positive, as they valued the model’s interactivity, flexibility, and motivational impact, especially through video-based preparation and in-class collaboration. Four main themes emerged: learning effectiveness, use of video lessons, time management, and English mastery. The study highlights that contextual factors moderate the flipped classroom’s success in Aceh. Despite these challenges, the results validate its relevance for Generation Z learners and support its wider adoption in Indonesian higher education. Future research is recommended to conduct longitudinal or comparative studies across regions to deepen understanding of the model’s long-term and contextual impacts.